Great saphenous vein cannulation as venous access for cardiopulmonary bypass for minimally invasive cardiac surgery (Indian Journal of Case Reports, 2020)
Minimally invasive cardiac surgery has seen the development of new techniques and modifications to achieve the goal. Arterial and venous cannulation is prime initial steps for establishing a good cardiopulmonary bypass to enable the main surgery. Usually, percutaneous cannulation is used but is costly; hence, most surgeons prefer an open surgical approach. Direct femoral venous cannulation is easy; however, if there is a tear in the femoral vein, usually on insertion or removal of the cannula, it can cause troublesome hemorrhage. A simple technique for venous cannulation with direct cannulation of the great saphenous vein has been described and does not require additional hardware and is expeditious. The method is safer, reliable, and repeatable and can be done easily even in emergency situations.